Pemberdayaan Kelompok Tuna Daksa “Baraka” melalui Inovasi Pengembangan Produk Daur Ulang Ban Bekas Guna Mendukung Reputasi Bisnis Kelompok Difabel: Empowerment of the "Baraka" Group with Physical Disabilities through Innovation in Developing Recycled Tire Products to Support the Business Reputation of Disabled Communities - Romadhan, Mohammad Insan; Kusnadi, Hajidah Fildzahun Nadhilah; Khoiroh, Siti Muhimatul (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
This community partnership program is the Empowerment of the "Baraka" Group with Physical Disabilities through Innovation in Developing Recycled Tire Products to Support the Business Reputation of Disabled Communities. The "Baraka" Group of People with Physical Disabilities is a group that runs a business recycling used tires into creative seating and table products. However, the group faces several challenges, including difficulties in production, such as a lack of ability to control the quality of the products, limited innovation in the products they develop, and lengthy production times. Socially, the group also faces a lack of motivation to create economic independence and has limited ability in branding their products. The implementation method involves mapping the necessary activities to address the challenges in these areas. The results of the program show that, in terms of production, the products produced by the group have started to meet quality and quantity standards. The product range has expanded, with chairs now available in small and large sizes, whereas previously, only medium sizes were available. Additionally, the group introduced table variants. Over the past week, the group was able to produce 10 products, indicating that on average, they could produce around 40 products in a month. Socially, awareness of economic independence has increased, and the group now has a logo and tagline to strengthen the reputation of their products. In terms of marketing, over the past week, the group received orders for 10 products, which suggests they could meet demand for around 40 products per month.